Molecular and morphological characterisation of Scutellonema bradys from yam in Costa Rica and development of specific primers for its detection - Humphreys-Pereira, D.; Williamson, V.; Lee, S.; Coyne, Danny L.; Salazar, L.; Gómez Alpízar, L. (Brill, 2014)
The yam nematode,Scutellonema bradys, which can cause dry rot disease of yam (Dioscoreaspp.), was recorded forthe first time from Costa Rica in four species of yam occurring in the Atlantic and north regions. Morphometric measurements fromtwo populations from each region using ten female and 11 male characters corresponded with previous descriptions of this species.Canonical discriminant analysis of the female morphometric data separated the populations by region, whereas no separation byregion was evident using the male data. Analysis of DNA sequences from the ITS region indicated that populations from Costa Ricawere monophyletic withS. bradysfrom West Africa and clearly distinct from otherScutellonemaspecies. No genetic separation bygeographic region orDioscoreaspecies host was observed between Costa Rica populations. Species-specific primers were developedfrom the ITS region and supported the identity of 17 populations from 15 locations in Costa Rica asS. bradys: 14 populations fromD. alata(greater or water yam) and one each fromD. trifida(white yampee),D. cayenensis(yellow yam) andD. rotundata(whiteyam). Yam production in Costa Rica began in the Atlantic region, where the yam nematode was likely introduced from the Caribbean,progressively spreading to other locations through the use of infected vegetative planting material.